2023
DOI: 10.1038/s41594-023-00928-6
|View full text |Cite
|
Sign up to set email alerts
|

Direct visualization of transcription-replication conflicts reveals post-replicative DNA:RNA hybrids

Abstract: Transcription-replication collisions (TRCs) are crucial determinants of genome instability. R-loops were linked to head-on TRCs and proposed to obstruct replication fork progression. The underlying mechanisms, however, remained elusive due to the lack of direct visualization and of non-ambiguous research tools. Here, we ascertained the stability of estrogen-induced R-loops on the human genome, visualized them directly by electron microscopy (EM), and measured R-loop frequency and size at the single-molecule le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 67 publications
3
29
0
Order By: Relevance
“…Since resection is a post-replicative process, this implies that RNase H-sensitive structures accumulate behind stressed forks and interfere with their processing and recovery. The existence of post-replicative RNA:DNA hybrids is also supported by a recent electron microscopy study showing that RNA:DNA hybrids accumulate behind bacterial forks at head-on TRCs in (Stoy et al, 2023). RNase H2 degrade different types of substrates, including RNA: DNA hybrids, RNA primers of Okazaki fragments and ribonucleotides erroneously incorporated into DNA.…”
Section: Rnase H1 and H2 Are Dispensable For Normal Fork Progression ...mentioning
confidence: 83%
See 1 more Smart Citation
“…Since resection is a post-replicative process, this implies that RNase H-sensitive structures accumulate behind stressed forks and interfere with their processing and recovery. The existence of post-replicative RNA:DNA hybrids is also supported by a recent electron microscopy study showing that RNA:DNA hybrids accumulate behind bacterial forks at head-on TRCs in (Stoy et al, 2023). RNase H2 degrade different types of substrates, including RNA: DNA hybrids, RNA primers of Okazaki fragments and ribonucleotides erroneously incorporated into DNA.…”
Section: Rnase H1 and H2 Are Dispensable For Normal Fork Progression ...mentioning
confidence: 83%
“…Alternatively, RNA:DNA hybrids may interfere with fork restart mechanisms acting behind stressed forks (Barroso et al, 2019;Svikovi c et al, 2019). The existence of postreplicative RNA:DNA hybrids is supported by a recent electron microscopy study showing that RNA:DNA hybrids are found behind and not ahead of arrested forks at bacterial TRCs (Stoy et al, 2023).…”
Section: Introductionmentioning
confidence: 97%
“…Alternatively, WRNIP1 may play a role in stabilizing RAD51 on the ssDNA of DNA/RNA hybrids, facilitating fork restart through fork reversal. Indeed, one proposed mechanism for processing DNA/RNA hybrids involves the exposure of ssDNA and the loading of RAD51, which mediates fork reversal (Stoy et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…While these hybrids are typically resolved under physiological conditions, allowing stalled fork restart (Stoy et al 2023;Chappidi et al 2020), post-replicative DNA/RNA hybrids could represent pathological TRC intermediates capable of impairing replication fork progression and stimulating fork reversal.…”
Section: Discussionmentioning
confidence: 99%
“…In E. coli, RNase HI suppresses double-strand break formation at sites of codirectional conflicts between DNA replication and transcription (22). Headon replication-transcription conflict is especially deleterious (7,(22)(23)(24)(25)(26), and RNase HIII may reduce R loop accumulation and mutation rates in head-on genes, potentially by helping to avoid replication fork reversal at head-on conflict sites (7,27). Assigning relative importance to the contributions and interplay of RDHs, replication-transcription conflict direction, gene expression level, R loop stability, gene location, and sequence context to mutagenesis has been difficult, in part because of the sheer number of biological inputs, and in part owing to the current lack of a highly specific, reproducible method for detecting R loops.…”
Section: Introductionmentioning
confidence: 99%